Institutional pressures and circular economy performance: The role of environmental management system and organizational flexibility in oil and gas sector. (23rd July 2020) - Jain, Nikunj Kumar; Panda, Abinash; Choudhary, Piyush
Abstract: The pressures to make business operations sustainable have been pushing organizations to adopt circular economy (CE) principles. With depleting fossil resources, the oil and gas (O&G) sector is pushed towards recycling limited resources available with it by leveraging CE principles. However, not many studies have been taken up how institutional pressures influence CE‐targeted environmental and economic performances. Drawing on institutional theory, this study examines the moderated‐mediation role of organization flexibility on the effects of institutional pressures on CE performance through environmental management systems (EMSs). Data are collected from 280 firms in Indian O&G sector using questionnaire‐based survey method. The study reveals that organizations leverage EMS to achieve CE performance, and flexible organizations compared with rigid ones are more effective in dealing with coercive pressures by leveraging EMS. These insights may help policymakers to formulate regulatory framework judiciously that encourages firms to adopt EMS in making their operations environmentally sustainable.